Evaluation of Drug Utilization Pattern among Geriatric Patients in a District Head Quarters Government Hospital using World Health Organization Indicators - McGrath, Rajasmith Paul; Arumugavignesh, Murugakadavul; Abishek, Rajaram; Afreeth, S. Uduman Mohamed; Ponraj, Nagendran; Vigneswaran, Rajagopal (Journal of Pharmacy Practice and Community Medicine)
Objectives: The aim of the study is to know about the drug utilization pattern among geriatric patients in a district headquarters government hospital using World Health Organization indicators. Among all age groups, geriatric patients are prescribed with more medicine and the possibility of the drug related problems also very high. Hence this study is conducted with a broad aim to understand the drug utilization pattern among geriatric patients. Methods: This is a cross-sectional prospective observational study involving 150 geriatric patients. All the patients are inpatients and no ambulatory patients were included in the study. It was a thirteen months study conducted between October 2018 and October 2019. Relevant information for analysis was obtained through accessing patient’s case sheets. Results: It was found that the patients in the age group of 60–65 years (45%) were more prevalent for the diseases. There was a male patient preponderance (63%) in our findings. The mean number of drugs per prescription was found to be 7 (normal value = 1.3 – 1.6). The antibiotics were prescribed in about 70% of prescription (normal value = 20 – 26.8). Polypharmacy was prevalent in 79% of total prescriptions. Majority of drugs were prescribed in generic names which was 92% (normal value = 100%). And all the drugs were only prescribed from essential medication list (normal value = 100%). Conclusion: This Study of drug utilization pattern helps in examining the quality of patient care and to promote the rational use of drugs. It also increases its importance in pharmacoepidemiological interventions.
Keywords: Antibiotics; Drug utilization pattern; Geriatrics; Injectables; Prescribing indicators; Polypharmacy.